Sa‘adah Haqiqiyyah: Solusi Filosofis al-Farabi Mengatasi Quarter Life Crisis dan Krisis Makna Generasi Muda - Mulyati, Sri (IAIN Manado, 2025)
Abstract: This study aims to examine the philosophical response to the phenomenon of quarter life crisis among young people through Al-Farabi’s thoughts on true happiness (sa‘adah haqiqiyyah). The quarter life crisis is analyzed as an existential crisis rooted in the trap of illusory happiness (sa‘adah majaziyyah), namely the pursuit of material success and external validation, exacerbated by digital pressures. This qualitative research uses a literature study method and a conceptual philosophical analysis approach to Al-Farabi’s works. The results show that the concept of sa‘adah haqiqiyyah offers a comprehensive solution by guiding individuals back to the highest goal (al-ghayah al-quswa) through the perfection of reason and morals. This solution is realized through two paths: The Theoretical Path (Al-Fikr al-Nazari) to achieve intellectual tranquility (ittisal) that overcomes confusion of meaning; and The Practical Path (Al-Fikr al-‘Amali) which requires the practice of four moral virtues and active participation in a virtuous social life (Madinah al-Fadilah) to overcome paralysis of action and inauthenticity. Theoretically, this study adds to the scientific knowledge about the relationship between quarter life crisis and Islamic philosophy. Due to methodological limitations (non-empirical), it is recommended that further research conduct empirical testing of the effectiveness of this concept as an Islamic counseling intervention. Keywords: Quarter Life Crisis, Al-Farabi, Happiness, and Sa’adah Abstrak: Penelitian ini bertujuan mengkaji respons filosofis terhadap fenomena quarter life crisis pada generasi muda melalui pemikiran al-Farabi tentang kebahagiaan sejati (sa‘adah haqiqiyyah). Quarter life crisis dianalisis sebagai krisis eksistensial yang berakar pada keterjebakan pada kebahagiaan semu (sa‘adah majaziyyah) yaitu pengejaran kesuksesan material dan validasi eksternal yang diperburuk oleh tekanan digital. Penelitian kualitatif ini menggunakan metode studi kepustakaan dan pendekatan analisis konseptual-filosofis terhadap karya-karya Al-Farabi. Hasilnya menunjukkan bahwa konsep sa‘adah haqiqiyyah menawarkan solusi komprehensif dengan menuntun individu kembali pada tujuan tertinggi (al-ghayah al-quswa) melalui penyempurnaan akal dan moral. Solusi ini diwujudkan melalui dua jalan: Jalan Teoretis (Al-Fikr al-Nazari) untuk mencapai ketenangan intelektual (ittisal) yang mengatasi kebingungan makna; dan Jalan Praktis (Al-Fikr al-‘Amali) yang menuntut pengamalan empat kebajikan moral dan partisipasi aktif dalam kehidupan sosial berbudi (Madinah al-Fadilah) untuk mengatasi kelumpuhan aksi dan inauthenticity. Secara teoritis, penelitian ini menambah khazanah keilmuan tentang hubungan antara quarter life crisis dan filsafat Islam. Karena keterbatasan metodologis (non-empiris), direkomendasikan penelitian selanjutnya melakukan pengujian empiris terhadap efektivitas konsep ini sebagai intervensi konseling Islam. Kata Kunci : Quarter Life Crisis, Al-Farabi, Kebahagiaan, dan Sa’adah